2005
DOI: 10.1111/j.1551-2916.2005.00717.x
|View full text |Cite
|
Sign up to set email alerts
|

Toughening of SiC with Ti3SiC2 Particles

Abstract: Composites in the SiC–TiC–Ti3SiC2 system were synthesized using reactive hot pressing at 1600°C. The results indicate that addition of Ti3SiC2 to SiC leads to improved fracture toughness. In addition, high microhardness can be retained if TiC is added to the material. The best combination of properties obtained in this study is KIc=8.3 MPa·m1/2 and Hv=17.6 GPa. The composition can be tailored in situ using the decomposition of Ti3SiC2. Ti3SiC2 decomposed rapidly at temperatures above 1800°C, but the decomposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Toughening SiC with Ti 3 SiC 2 dispersions was also investigated. 298 The addition of Ti 3 SiC 2 to SiC led to improved fracture toughness, with the best combination of properties obtained to be a K IC 58?3 MPa m 1/2 and an HV517?6 GPa. Conversely, it is possible to reach a combination of hardness and fracture toughness by controlling the decomposition of Ti 3 SiC 2 to various binary carbides.…”
Section: Max-mx and Max-axmentioning
confidence: 95%
See 1 more Smart Citation
“…Toughening SiC with Ti 3 SiC 2 dispersions was also investigated. 298 The addition of Ti 3 SiC 2 to SiC led to improved fracture toughness, with the best combination of properties obtained to be a K IC 58?3 MPa m 1/2 and an HV517?6 GPa. Conversely, it is possible to reach a combination of hardness and fracture toughness by controlling the decomposition of Ti 3 SiC 2 to various binary carbides.…”
Section: Max-mx and Max-axmentioning
confidence: 95%
“…Toughening SiC with Ti 3 SiC 2 dispersions was also investigated 298. The addition of Ti 3 SiC 2 to SiC led to improved fracture toughness, with the best combination of properties obtained to be a K IC = 8·3 MPa m 1/2 and an HV = 17·6 GPa.…”
Section: Materials and Processes Based On Max Phasesmentioning
confidence: 99%
“…Aside from the control sample, Ti3SiC2 intermetallic was present in XRD spetra of all the sintered composite speimens. Primarily, Ti3SiC2 is a hard carbide with dual properties of metal and ceramic, which makes it an exceptional material with better combination of thermal and mechanical property than monolithic titanium [23][24][25][26][27][28]. Furthermore, it has a superior thermal shock resistance, higher temperature oxidation resistance, superior fracture toughness and better damage resilience compared to titanium.…”
Section: Phase (Xrd) Analysismentioning
confidence: 99%
“…10,11 Furthermore, Ti 3 SiC 2 is an excellent electrical conductor (conductivity: 9?6610 6 V 21 m 21 at room temperature), good thermal conductor (conductivity: 37 W m 21 K 21 at room temperature) and not susceptible to thermal shock. [12][13][14][15] A number of studies have been reported on the synthesis of single phase Ti 3 SiC 2 powder, bulk material and relative composites. Many synthesis methods have been employed including hot pressing, hot isostatic pressing, self-propagating high temperature synthesis, mechanical alloying, spark plasma sintering (SPS), etc.…”
Section: Introductionmentioning
confidence: 99%